The relevance of social capital and intermediary structures for the creation of systemic competitiveness - Adam, Frane (Družboslovne razprave, 1998)
The autor proceeds from the thesis that (post-socialist) countries which demand to be members of the EU will attain a position of compatibility and isomorpolism with a modernised core only if they develop - parallel to the acceptance of formal rulles and regulations - also the organisations, associations and mechanism which belong the tipe so-colled intermediary sphere (from NGO-s to various mediating bodies and project groups). In this context the notion of social capital is underlined and the reasons for the nowdegree of trust and cooperation (as two main ingredients of this capital) are analysed.
Keywords: Eastern Europe; Vzhodna Evropa; Srednja Evropa; Central Europe; postsocializem; tranzicija; integracija; mednarodno sodelovanje; politične razmere; družbeni razvoj; družbene spremembe